ANALISIS KESALAHAN PEMILIHAN KATA DALAM PROSES PEMBELAJARAN BAHASA INDONESIA SISWA KELAS X SMA SWASTA KAMPUS TELUK DALAM - Kurnianus Halawa (Universitas Nias Raya, 2026)
Based on initial observations conducted in the 10th grade of SMA Swasta Kampus Teluk Dalam, there are still errors in word choice when students speak. The purpose of this study is to describe lexical choice errors in the Indonesian language learning process of 10th grade students at SMA Swasta Kampus Telukdalam in the 2023/2024 academic year. This research uses a qualitative approach with a descriptive method. The data sources in this study were taken from the results of video recordings of student conversations. The subjects in this study were 10th grade students at SMA Swasta Kampus Telukdalam in the 2023/2024 academic year. The data collection technique used in this study was audio recording. The data analysis technique in this study was data reduction, data presentation, and conclusion drawing (verification). Based on the presentation of the research findings on the analysis of lexical choice errors in the learning process of students at SMA Swasta Kampus Telukdalam in the 2023/2024 academic year, the researcher concludes that the lexical choice errors include synonyms, antonyms, and hyponyms. There were nine errors in the choice of synonyms, two errors in the choice of antonyms, and one error in hyponyms. The dominant lexical choice error in this study was synonyms. The conclusion of the researcher's findings on lexical choice errors in the Indonesian language learning process of 10th grade students at SMA Swasta Kampus Telukdalam in the 2023/2024 academic year. This research can be used as a reference or example for teachers and as a learning experience in schools, especially for the Indonesian language subject regarding lexical choice errors. It is hoped that all language users will be able to choose the right words when using language, especially in formal meetings.